2020
DOI: 10.2106/jbjs.oa.19.00057
|View full text |Cite
|
Sign up to set email alerts
|

TightRope Versus Biocomposite Interference Screw for Fixation in Allograft ACL Reconstruction

Abstract: ShahThe purpose of this form is to provide readers of your manuscript with information about your other interests that could influence how they receive and understand your work. The form is designed to be completed electronically and stored electronically. It contains programming that allows appropriate data display. Each author should submit a separate form and is responsible for the accuracy and completeness of the submitted information. The form is in six parts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
(23 reference statements)
1
7
0
Order By: Relevance
“…The degree of flexion 6 months after surgery was 132° and 136° for the IF- and PFH-group, respectively. This confirms the findings of Yari et al [ 47 ] The PFH-group showed significantly ( p = 0.00529) better results at more than 100 days post-surgery, providing patients with increased mobility. This might be attributed to faster healing in the PFH-group, as a result of a primarily biological reconstruction of the ACL without metal or resorbable screws.…”
Section: Discussionsupporting
confidence: 91%
“…The degree of flexion 6 months after surgery was 132° and 136° for the IF- and PFH-group, respectively. This confirms the findings of Yari et al [ 47 ] The PFH-group showed significantly ( p = 0.00529) better results at more than 100 days post-surgery, providing patients with increased mobility. This might be attributed to faster healing in the PFH-group, as a result of a primarily biological reconstruction of the ACL without metal or resorbable screws.…”
Section: Discussionsupporting
confidence: 91%
“…Detailed search process is illustrated in Fig 1 . These included trials were published between 2002 and 2020, with 9 trials of CB vs CP [ 14 , 29 , 36 , 37 , 42 , 43 , 46 , 48 , 51 ], 9 of CB vs IS [ 18 , 30 33 , 35 , 44 , 45 , 50 ], and 8 of CP vs IS [ 16 , 34 , 38 41 , 47 , 49 ]. Follow-up time ranged from 6 months to 60 months.…”
Section: Resultsmentioning
confidence: 99%
“…The TightRope ® system is a kind of suture tape that is commonly used in treating acromioclavicular joint dislocation 39,40 and in other kinds of fixation. [41][42][43][44][45][46] It is a minimally invasive fixation method with sufficient stability. The technique of fixation with the TightRope ® system is simpler than that with IS screws and has no risk of nerve root injury.…”
Section: Discussionmentioning
confidence: 99%
“…Our technique utilized TightRope® system fixation, which is a new way to stabilize the posterior pelvic ring. The TightRope® system is a kind of suture tape that is commonly used in treating acromioclavicular joint dislocation 39,40 and in other kinds of fixation 41–46 . It is a minimally invasive fixation method with sufficient stability.…”
Section: Discussionmentioning
confidence: 99%